A Process Evaluation of the Academic Component of the Hope Scholars Programme (HSP) - Miyoba, Erwin (Organisational Psychology, 2020)
The Hope Scholars Programme (HSP) is an after-school programme implemented by the South African Education and Environment Project (SAEP) in Cape Town, South Africa. After-school programmes (ASPs) are widely described as programmes that are implemented independently of the school day and are aimed at improving the learning outcomes and advancement of kindergarten and high school learners. The HSP began in 1998 with a goal to equip HSP learners with foundational literacy and numeracy skills for the future education and training (FET) phase and subsequent education. HSP activities are implemented under four broad service areas: (a) academic tutoring sessions; (b) experiential learning; (c) psychosocial support services; and (d) community engagement. The scope of this evaluation was the academic component under which the programme offers intensive tutoring in mathematics, natural science and English literacy. The objective of the evaluation was to assess the implementation fidelity of the academic component for programme quality and effectiveness improvement purposes. A conceptual framework for measuring implementation fidelity by Carroll, Patterson, Wood, Booth, Rick and Balain (2007) was used to guide this evaluation. Using the logic model for the programme, the evaluation focused on examining whether the HSP sessions were implemented with the intended process mechanisms through which the programme was designed to lead to its desired academic outcomes. Both primary and secondary data were used to conduct the evaluation. Primary data were collected through oneon-one in-depth interviews with HSP staff members and the volunteer tutor and focus group interviews with the HSP learners. Secondary data were obtained through the review of the HSP documents. An inductive content analysis was employed to analyse the data. The results indicated that the academic component of the HSP was implemented with limited fidelity and poor quality. Programme implementation challenges identified need to be resolved to enhance the quality of the HSP services and programme effectiveness. This evaluation contributes to the literature on: (a) the duration and frequency of the tutorial sessions; (b) the extent to which learners attend; and (c) dropout from the programmes and causes for dropping out in the context of after-school programmes. Among the contributing factors of learner dropout from the HSP, influences that were found unique to the South African context were mistrust between the learners and their parents (mistrust at home) and sweeping of classrooms.